2022
DOI: 10.1039/d2re00117a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insight into the photocatalytic degradation of organic pollutants and electrochemical behavior of modified MWCNTs/Cu–Co3O4 nanocomposites

Abstract: The present work reported, the synthesis of pure Co3O4 and Cu-Co3O4 nanocrystals by (Polyethylene glycol) PEG-assisted microwave heating route. Crystallinity, morphology, elemental composition, optical, and electrical properties of the as-synthesized...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…This suggests that photogenerated holes (h + ) and electrons (e − ) are another efficient species in the degradation of methylene blue, along with hydroxyl radicals and superoxide anion radicals. 27…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that photogenerated holes (h + ) and electrons (e − ) are another efficient species in the degradation of methylene blue, along with hydroxyl radicals and superoxide anion radicals. 27…”
Section: Resultsmentioning
confidence: 99%
“…Thus, sunlight was used for the photocatalytic degradation of dye. 27 The results showed that the photocatalytic degradation efficiency was improved in 90 minutes of reaction by increasing the concentration of Cu from 0.10 M to 0.20 M in the crystallite lattice of CuTiO 3 . As seen in Fig.…”
Section: Photocatalytic Evaluationmentioning
confidence: 96%
See 1 more Smart Citation
“…33 Based on the results, a further study on dye photodegradation will be carried out at pH 7 of the dye solution using 0.06 M Mg–Sr codoped ZnO catalyst dose of 15 mg and the initial concentration of the LO dye solution at 20 ppm and 180 min of sunlight irradiation. 34…”
Section: Photocatalytic Activitiesmentioning
confidence: 99%
“…1,2 These pollutants may cause serious threats to ecological and environmental systems, and further affect aquatic life and human health. 3 Moreover, due to their special chemical structures and π-conjugated systems, most dye pollutants are difficult to be degraded by conventional physicochemical and biological methods. 4,5 Thus, the efficient removal of these pollutants has attracted considerable research attention from researchers due to their ecological and environmental impacts.…”
Section: Introductionmentioning
confidence: 99%